PENERAPAN MODEL PEMBELAJARAN MATEMATIKA TERHADAP HIGHER ORDER THINKING SKILLS (HOTS) SISWA KELAS IV MI NEGERI PUNGGELAN BANJARNEGARA TAHUN PELAJARAN 2017/2018 - HARYANTO, ANDRI; MULYANI, PAMUNGKAS STIYA (AL-QALAM: JURNAL KEPENDIDIKAN, 2019)
This study aims to determine the learning process with a realistic mathematical learning model that is applied to improve students 'HOTS and to determine the effect of a realistic mathematics learning model on students' HOTS. This study uses a quantitative approach with a quasi-one group experiment, with a sample of 30 students, this sample was taken from the population of all MI Negeri Punggelan Banjarnegara students in the academic year 2017/2018. Research data in the form of high-level students' ability to think from the results of multiple choice questions. The analysis technique used is quantitative analysis with the "t" test. From the research results obtained tcount = 14.711> ttable = 2.045 with a significance level of 5%. From the hypothesis test, then H0 was rejected and Ha was accepted, which means that this study proves that mathematics learning using realistic mathematics learning models has an effect on the ability to think high level (HOTS) grade IV students in MI Negeri Punggelan Banjarnegara academic year 2017/2018